Manufacturing and Shear Response Characterization of Carbon Nanofiber Modified CFRP Using the Out-of-Autoclave-Vacuum-Bag-Only Cure Process - Erin E. McDonald; Landon F. Wallace; Gregory J. S. Hickman; Kuang-Ting Hsiao (The Scientific World Journal)
The interlaminar shear response is studied for carbon nanofiber (CNF) modified out-of-autoclave-vacuum-bag-only (OOA-VBO) carbon fiber reinforced plastic (CFRP). Commercial OOA-VBO prepregs were coated with a CNF modified epoxy solution and a control epoxy solution without CNF to make CNF modified samples and control samples, respectively. Tensile testingwas used to study the in-plane shear performance of [±45°]4s composite laminates. Significant difference in failure modes between the control and CNF modified CFRPs was identified. The control samples experienced half-plane interlaminar delamination, whereas the CNF modified samples experienced a localized failure in the intralaminar region. Digital image correlation (DIC) surface strain results of the control sample showed no further surface strain increase along the delaminated section when the sample was further elongated prior to sample failure. On the other hand, the DIC results of the CNF modified sample showed that the surface strain increased relatively and uniformly across the CFRP as the sample was further elongated until sample failure. The failure mode evidence along with microscope pictures indicated that the CNF modification acted as a beneficial reinforcement inhibiting interlaminar delamination.